A dynamic theory of forward exchange - Einzig, Paul. (London : Macmillan ; New York : St. Martin's Press, 1961)
The book discussed the forward exchange; the realization of the extent to which the existence and use of forward exchange facilities played a decisive role in past economic developments capable of disturbing the economy in the future.
Includes bibliographical references and index.
rua 02/06/17
Loans
Keywords: Foreign exchange